Pengaruh TQM dan Kualitas Pelayanan Kesehatan terhadap Kepuasan Pasien serta Implikasinya kepada Kinerja Pegawai UPTD Puskesmas Jeumpa Kabupaten Bireuen - Zakaria, Zakaria; Syahriani, Endang (Aceh Cooperative Care, 2024)
Research was conducted on UPTD patients at Jeumpa Public Health Center, Bireuen Regency with the aim of empirically analyzing the influence of TQM and health service quality on patient satisfaction and its implications for employee performance. Survey research using questionnaire instruments with associative quantitative methods. Respondents totaled 92 patients at a significance level of 5%. Results obtained: 1) There is a direct and indirect effect of TQM on patient satisfaction of 38.08%. 2) There is a direct and indirect influence of the quality of health services on patient satisfaction of 27.49%. 3) Simultaneously TQM and service quality contribute to patient satisfaction of 72.8%, 4) There is an influence of patient satisfaction on employee performance of 70.9%. 5) There is a direct and indirect influence of TQM on employee performance of 29.69%. 6) There is a direct and indirect influence of the quality of health services on employee performance of 31.27%. 7) Simultaneously the contribution of TQM and service quality to employee performance is 74.8%.